Brain Microbial Populations in HIV/AIDS: α-Proteobacteria Predominate Independent of Host Immune Status - Branton, William G. (Public Library of Science, 2013)
The brain is assumed to be a sterile organ in the absence of disease although the impact of immune disruption is uncertain in terms of brain microbial diversity or quantity. To investigate microbial diversity and quantity in the brain, the profile of infectious agents was examined in pathologically normal and abnormal brains from persons with HIV/AIDS [HIV] (n = 12), other disease controls [ODC] (n = 14) and in cerebral surgical resections for epilepsy [SURG] (n = 6). Deep sequencing of cerebral white matter-derived RNA from the HIV (n = 4) and ODC (n = 4) patients and SURG (n = 2) groups revealed bacterially-encoded 16 s RNA sequences in all brain specimens with α-proteobacteria representing over 70% of bacterial sequences while the other 30% of bacterial classes varied widely. Bacterial rRNA was detected in white matter glial cells by in situ hybridization and peptidoglycan immunoreactivity was also localized principally in glia in human brains. Analyses of amplified bacterial 16 s rRNA sequences disclosed that Proteobacteria was the principal bacterial phylum in all human brain samples with similar bacterial rRNA quantities in HIV and ODC groups despite increased host neuroimmune responses in the HIV group. Exogenous viruses including bacteriophage and human herpes viruses-4, -5 and -6 were detected variably in autopsied brains from both clinical groups. Brains from SIV- and SHIV-infected macaques displayed a profile of bacterial phyla also dominated by Proteobacteria but bacterial sequences were not detected in experimentally FIV-infected cat or RAG1(−/−) mouse brains. Intracerebral implantation of human brain homogenates into RAG1(−/−) mice revealed a preponderance of α-proteobacteria 16 s RNA sequences in the brains of recipient mice at 7 weeks post-implantation, which was abrogated by prior heat-treatment of the brain homogenate. Thus, α-proteobacteria represented the major bacterial component of the primate brain’s microbiome regardless of underlying immune status, which could be transferred into naïve hosts leading to microbial persistence in the brain.